FISH COMMUNITY STRUCTURE IN THE MIDDLE OF BRANTAS RIVER, EAST JAVA, INDONESIA - Kristina Marsela; Arief Setyanto; Mihrobi Khalwatu Rihmi; Alfi Robiansyah; Viga Ballacka Irawan; Gatut Bintoro; Tri Djoko Lelono; Andik Isdianto (Universitas Mataram, 2026)
Fish are important biological indicators used to determine the health of an ecosystem. Fish community structure is dynamic and influenced by various environmental pressures. Changes in fish community structure in river ecosystems, such as in the waters of the Brantas River, East Java, can reflect the ecological conditions of these waters. The objective of this study was to evaluate the fish community structure in the middle section of the Brantas River based on ecological indices, including relative abundance, diversity, evenness, and species dominance. The research method was conducted through surveys of local fishermen's catches at six observation stations in the middle section of the Brantas River, covering the Tulungagung to Kediri area, from July to September 2024. The ecological index values showed moderate diversity (H' 1.16–1.80), relatively high evenness (E 0.83–0.95), and low to moderate dominance (C 0.18–0.33). Based on the results of this study, it shows that the fish community in the middle section of the Brantas River is still in the moderate diversity category with good distribution, but there are indications of dominant species in certain locations and the presence of introduced species that require attention in monitoring and sustainable management.